Framework aplicável em políticas de gestão dos resíduos de equipamentos elétricos e eletrônicos (REEE) nos países do BRICS - Franz, Nadia Mara (2023)
Industrialization, urbanization and the increase in consumption of electronics, which associated with the short life cycles of this equipment, recycling complexity and limited physical and legal infrastructure, generate an exponential increase in Waste Electrical and Electronic Equipment (WEEE), especially in large cities. In recent years, WEEE has grown three times faster than the world’s population and 13% more than the world’s GDP. In 2019, a record 53.6 Mt was recorded, of which only 17.4% was properly disposed of. China, India, and the United States are responsible for 38% of the world’s disposal of WEEE. Brazil, in turn, is among the world’s largest producers of electronics, but it is the fifth largest generator of WEEE in the world, with recycling of less than 3% and per capita generation of 10.2 kg/year. In this scenario, the question that guides the objectives of this thesis is expressed in: what factors are important to the development of propositions applicable in policies and actions for the sustainable management of WEEE based on the principles of the circular economy within the scope of the BRICS countries? The BRICS grouping is formed by Brazil, Russia, India, China and South Africa, which represent about 41.15% of the world’s population, 30% of the global territory and 25.71% of the world’s GDP in 2021. This research has the central objective of presenting a framework for the development of propositions applicable in policies and actions for the sustainable management of WEEE based on the principles of circular economy within the BRICS countries. The research methodology uses a qualitative approach of an applied nature, employs bibliographical and documentary research techniques and semi-structured interviews in the multiple case study method, whose analytical technique is content analysis and cross-case synthesis. The results of this thesis demonstrate the legal and institutional compositions of WEEE management in BRICS countries, identifies the different actors in the processes inherent to WEEE, structures important theoretical aspects of positive results in WEEE management in BRICS and; validates these theoretical propositions in an interview with 16 technical and scientific specialists from the BRICS selected in an intentional sample. In this sense, the thesis infers the relevance of legislation to the management of WEEE and the protagonism of government levels, especially in metropolises, in articulating the parties involved in synergy in the management of environmental and human health risks and in the implementation of inclusive systems of producer responsibility, acting to raise society’s awareness of sustainable consumption and the reduction and proper disposal of WEEE and; stimulating economically viable circular business models that promote the development of the market for secondary resources and provide opportunities for social inclusion. The research infers that even when analyzing countries with different cultural characteristics, institutional structures can normalize policies and actions aimed at WEEE management, based on the principles of the circular economy, which, in turn, can act as a driving force in promoting sustainable development. Territories, balancing economic growth, social progress and a healthy environment.